ATTITUDES OF FOOTBALL PLAYERS OF DIFFERENT AGE ON TRAINING EXERCISES OF RECOVERY - Miroslav Smajić; Bogdan Tomić; Miroslav Radoman; Peko Vujović; Goran Ivančić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Training exercises of recovery of sportsmen include both exercises implying higher level of training and exercises of optimal recovery of sportsmen. In order to use training exercises of recovery best way it is necessary to know how they react to the body of a sportsman concerning their character and length. It is also necessary to take into consideration the fact that human body adapts equally both to burden and adequate recovery exercises. To increase the efficiency of training exercises of recovery it is inevitable to use different exercises and methods changing their use, that is, they should be applied in a complex way considering their change depending on sport activities and structure of training process. The aim of the study is to check and analyse attitudes of football players of different age on training exercises of recovery. The sample of examinees consists of 120 players from nine different clubs from the area-level competition of the Football Association of Vojvodina (Serbian Super League = 43, first division = 40 Serbian and Serbian league = 37), which were divided into two groups according to age (group I (65 ) - 18-25 years age group II (55) - over 25 years of age). The sample of variables consists of the system of 10 attitudes (claims), and each attitude (claim) consists of 5 verbal categories (marked from -2 to +2). To determine the significance of differences between players of different ages multivariate analysis of variance were used (MANOVA), univariate analysis of variance (ANOVA), discriminative analysis and Roy's test. All sample of examinees is unique in a larger number attitudes towards the training exercises of recovery, determined statistical differences can be attributed to a better understanding of the recovery process by a group of older players.